A Lexical Semantic Analysis of Love And Loss in Lord Huron's "The Night We Met" - Amri, Ghalib; Djuharie, Otong Setiawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study explores the semantic fields of love and loss in Lord Huron’s song "The Night We Met," using a lexical semantics framework. Song lyrics, known for their emotional depth, serve as a rich source for analyzing affective meaning, particularly through word selection and repetition. The primary research question addresses how semantic fields are constructed within minimalist lyrical compositions to convey complex emotional states. In this analysis, a qualitative descriptive method is applied to examine the song's lexical items and group them into thematic semantic fields. The study finds that the song uses a concise set of lexemes connected to themes of memory, temporal disorientation, grief, and love. These thematic fields intertwine, interacting to depict a narrative that encapsulates unresolved emotional pain. Love and loss are not presented in isolation but are embedded in a broader emotional context, where words evoke both the sweetness of past affection and the sorrow of its absence. The overlap of these semantic fields reflects the internal conflict experienced by the narrator, torn between cherished memories and the painful realization of loss. The study concludes that despite the song’s brevity, the lyrics effectively evoke profound emotional responses through a meticulous choice of words and thematic consistency. The semantic fields constructed within the song illustrate how even minimal language can convey intense emotional content, providing valuable linguistic insight into the function of lyricism in popular music. The research demonstrates the ability of short, poignant lyrics to engage listeners emotionally, revealing how lyricists use limited language to encapsulate complex feelings of love and loss.